2020
DOI: 10.1039/c9tc05487a
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the composition dependency of the ground-state structure, electronic property and phase-transition dynamics in ternary transition-metal-dichalcogenide monolayers

Abstract: Structural and electronic transition in the ternary TMD monolayer via doping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…At the same time, this effect is gradually weakened from the fourth subgroup metal to the sixth subgroup metal. 85 Based on the above work, the question arises as to whether it can be predicted that the phase transition can be effectively promoted only in the environment of alkali metal ions without the metal substitution doping. The conjecture has been proven by observing the change of TMDs in an environment full of alkali metal ions.…”
Section: Strategies To Improve the Her Activities Of Tmdsmentioning
confidence: 99%
“…At the same time, this effect is gradually weakened from the fourth subgroup metal to the sixth subgroup metal. 85 Based on the above work, the question arises as to whether it can be predicted that the phase transition can be effectively promoted only in the environment of alkali metal ions without the metal substitution doping. The conjecture has been proven by observing the change of TMDs in an environment full of alkali metal ions.…”
Section: Strategies To Improve the Her Activities Of Tmdsmentioning
confidence: 99%
“…Group VI transition metal dichalcogenides (TMDs or TMDCs) are a class of layered materials discovered during the last century [1][2][3][4]. Due to the fact that they find application in a wide range of technological areas, they have been the focus of intense research more recently (for example, [5][6][7][8][9][10]). Stable TMDCs (approximately 60 in number) have the generic formula AB 2 , [11,12], where A is a transition metal and B is chalcogen (S, Se, Te).…”
Section: Introductionmentioning
confidence: 99%
“…33 Diffusion of the chalcogen atom is believed to play a vital role in the phase transition of TMDC. 34 It has been shown that the 2H-to-1T′ phase transition can be initiated by the local ordering of Te vacancies driven by photogenerated excited carriers. 35 Besides, it has been shown that the atomic diffusion in TMDC vdW heterojunctions strongly modifies their optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…By combining scanning transmission electron microscopy (STEM) analysis, electrochemical study, and theoretical modeling, Xu et al revealed that S vacancies can act as preferential intercalation sites for the zinc ions, leading to a much greater capacity of zinc than that in defect-free MoS 2 . Diffusion of the chalcogen atom is believed to play a vital role in the phase transition of TMDC . It has been shown that the 2H-to-1T′ phase transition can be initiated by the local ordering of Te vacancies driven by photogenerated excited carriers .…”
Section: Introductionmentioning
confidence: 99%